Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.1 Definition of the Derivative - Exercises - Page 103: 19



Work Step by Step

$g'(t)=\lim\limits_{h \to 0}\frac{g(t+h)-g(t)}{h}=\lim\limits_{h \to 0}\frac{[8-3(t+h)]-[8-3t]}{h}$ $=\lim\limits_{h \to 0}\frac{8-3t-3h-8+3t}{h}=-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.